STRUCTURE OF THE TAIL OF A PHYTOSAUR (REPTILIA, ARCHOSAURIA) FROM THE NORIAN (LATE TRIASSIC) OF LOMBARDY (NORTHERN ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1999)
The structure of the caudal portion of a vertebral column belonging to a complete phytosaur skeleton is described. The skeleton has been collected from the Calcare di Zorzino (Zorzino Limestone) of Norian (Late Triassic) age, in the small quarry of Endenna (Bergamo, Lombardy, Northern Italy). The specimen is currently being prepared, and only a detailed description of the tail is possible. The exposed portion of the skull, which shows, among other characters, a narrow, flattened snout, suggests possible relationships with the genus Mystriosuchus, but preparation of the skull must be finished prior to attempting any classification. The morphology of the tail vertebrae has never been figured for phytosaurs; however, the structure of the tail vertebrae of this specimen reflects a great degree of adaptation toward aquatic life, justifying its description prior to complete preparation. If this specimen represents a new species, it should have been highly specialised toward marine life than most other phytosaurs in which the postcranial skeleton is known.